Issues in Performance Evaluation of New TCP Stacks in High Speed Networks - Saverio Mascolo; Francesco Vacirca (Proceedings of the 2005 International Symposium on Performance Evaluation of Computer and Telecommunication Systems (SPECTS’05), 2005)
TCP congestion control has been designed to ensure Internet stability along with fair and efficient allocation of the network bandwidth. With the spreading of high-speed and long-distance networks, the standard TCP congestion control algorithm showed some limitations in exploiting full bandwidth utilization. During the last few years, many new congestion control algorithms have been proposed to improve the classic Reno/NewReno TCP congestion control in such networks. This paper aims at comparing some of the most promising proposals and at investigating the relation between these new congestion control proposals and different bottleneck buffer provisioning rules.
Presented at the 2005 International Symposium on Performance Evaluation of Computer and Telecommunication Systems (SPECTS’05), July 2005